Magnitude of Self-Reported Syndromes of Sexually Transmitted Infections and Its Associated Factors Among Young Incarcerated Persons (18–29 Years) in Correctional Facilities of Gamo Gofa Zone, Southern Ethiopia - Getachew M; Haile D; Churko C; Alemayehu Gube A (Dove Medical Press, 2021)
Muluken Getachew,1 Dereje Haile,2 Chuchu Churko,3 Addisu Alemayehu Gube4 1Gofa Zone Health Department, Gofa, Southern Ethiopia; 2Reproductive Health and Nutrition Department, School of Public Health, College of Medicine and Health Sciences, Wolaita Sodo University, Sodo, Southern Ethiopia; 3Department of Public Health, School of Public Health, College of Medicine and Health Science, Arba Minch University, Arba Minch, Southern Ethiopia; 4Department of Public Health, College of Medicine and Health Science, Dilla University, Dilla, Southern EthiopiaCorrespondence: Dereje Haile Email derehaile2010@gmail.comBackground: Sexually transmitted infection is an infection that is typically transmitted by sexual contact and may either end or develop into a sexually transmitted disease. Today, young people are recognized as groups with special health-related vulnerabilities like drug use, unprotected sex and sexually transmitted infections. Despitea number of strategies which focused on young people’s health, there was limited evidence of sexually transmitted infection among young incarcerated persons. Thus, the aim of this study was to assess the self-reported syndromes of sexually transmitted infections and associated factors among young incarcerated persons (18– 29 years) in correctional facilities of the Gamo Gofa Zone, Southern Ethiopia.Methods: A facility-based cross-sectional study was conducted from March 1 to 15, 2019. Simple random sampling was used to select a total of 414 prisoners. The data were entered into Epi.info version 7 and exported and analyzed using SPSS version 20. Bivariate and multivariate logistic regression analysis were carried out. Statistical significance was declared by using the p value of < 0.05 at 95% confidence interval.The Results: In this study, 403 respondents participated with the response rate of 97.3%. The overall prevalence of self-reported STIs was 35 (8.7%). STI syndromes before incarceration (AOR: 5.267 (95% CI: 1.863, 14.893)), not having family support (AOR; 6.645 (95% CI: 2.327, 18.975)), history of imprisonment (AOR; 2.871 (95% CI: 1.065, 7.42)), not always using condom (AOR; 7.417, (95% CI 2.526, 21.781)), alcohol use (AOR; 5.926, (95% CI 2.282, 15.392)), chat use (AOR; 4.736, (95% CI (1.387, 16.172)) and having sex with commercial sex workers (AOR; 2.764, (95% CI 1.034, 7.388)) were significantly and independently associated with self-reported STIs.Conclusion: Prevalence of self-reported syndromes of STI was high. Attention is needed about sexually transmitted infections for incarcerated young people by concerned bodies, including governmental and non-governmental organizations.Keywords: STI, sexually transmitted infection, young, prison, Ethiopia